Application of Power Point Interactive Media to improve Student Activities and Learning Outcomes - Deni Darmawan; Wulan Nurfitri (PEDAGOGIA, 2022)
This research has a background of low student learning outcomes in grade 5 theme 6 at SDN I Barusuda, sub-district, Garut City. It is known that students have daily test scores that do not reach the specified KKM score.The purpose of this study was to increase the activity and learning outcomes of students by using interactive media PowerPoint for students of Class V Theme 6 at SDN I Barusuda, Cigedug District, Garut Regency. The research method using Classroom Action Research (CAR) consisting of 3 cycles with 4 stages, namely planning, action, observation, and reflection. The subjects of this study is students of class V with a total of 30 people. Data collection techniques useing observation, interviews, tests, and documentation. While the data analysis technique used descriptive analysis. The results of this study indicate that the average percentage of student activity classically has increased. In the pre-cycle before treatment, it was 65%, in the first cycle it was 69%, in the second cycle, it was 74% while in the third cycle it was 87%. While the percentage of mastery learning outcomes in the pre-cycle is 33%, in the first cycle it is 33%, in the second cycle, it is 73%, while in the third cycle it is 90%. Based on the results of the research that has been done, it can be concluded that learning in Theme 6 using interactive PowerPoint media can increase students' activities and learning outcomes.